Effect of malnutrition on the postoperative outcomes of patients undergoing pancreatectomy for pancreatic cancer: Propensity score–matched analysis of 2011–2017 US hospitals. (7th January 2022) - Lee, David Uihwan; Hastie, David Jeffrey; Fan, Gregory Hongyuan; Addonizio, Elyse Ann; Lee, Ki Jung; Han, John; Karagozian, Raffi
Abstract: Background: Patients with pancreatic cancer suffer from metabolic dysregulation, which can manifest in clinical malnutrition. Because a portion of these patients require cancer‐resective surgery, we evaluate the impact of malnutrition in patients undergoing pancreatic resection using a national database. Methods: The 2011–2017 National Inpatient Sample was used to isolate cases of pancreatic resection (partial/total pancreatectomy and radical pancreaticoduodenectomy), which were stratified using malnutrition. A 1:1 nearest‐neighbor propensity‐score matching was applied to match the controls to the malnutrition cohort. End points include mortality, length of stay (LOS), hospitalization costs, and postoperative complications. Results: Following the match, there were 2108 with malnutrition and an equal number without; from this, those with malnutrition had higher mortality (4.7% vs 3.04%; P = 0.007; odds ratio [OR], 1.57; 95% CI, 1.14–2.17), longer LOS, and higher costs. Regarding complications, malnourished patients had higher bleeding (5.41% vs 2.99%; P < 0.001; OR, 1.86; 95% CI, 1.36–2.54), wound complications (3.75% vs 1.57%; P < 0.001; OR, 2.45; 95% CI, 1.62–3.69), infection (7.83% vs 3.13%; P < 0.001; OR, 2.63; 95% CI, 1.96–3.52), and respiratory failure (7.45% vs 3.56%; P < 0.001; OR, 2.18; 95% CI, 1.65–2.89). In multivariate analyses, those with malnutrition had higher mortality ( P = 0.008; adjust OR, 1.55; 95% CI, 1.12–2.14). Conclusion: Those with malnutrition had higher mortality and complications following pancreatic resection; given these findings, it is important that preoperative nutrition therapy is provided to minimize the surgical risks.